OPERASIONALISASI PRODUK TABUNGAN MUDHARABAH DAN APLIKASINYA DI BRI SYARIAH CABANG SURABAYA DALAM PERSPEKTIF HUKUM ISLAM - Yazid, Muhammad (El-Qist: Journal of Islamic Economics and Business (JIEB), 2012)
This paper is the result of field research on the operationalization of mudharabah savings product and the reasons for its application in Bank Rakyat Indonesia (BRI) Sharia branch of Surabaya. This study aims to answer questions about the operationalization of mudharabah savings product at BRI Sharia branch of Surabaya and the reasons for the application of the savings product in the bank, as well as how the Islamic legal review of the the operationalization of mudharabah savings product at BRI Sharia branch of Surabaya and the reasons for its application. In this study, the method used is verificative descriptive which illustrates the operationalization of savings product and the reasons for its application in the Surabaya branch of BRI Sharia and then performed an assessment of that operationalization. From the results of the study can be obtained that the operationalization of savings product at BRI Sharia Surabaya branch of has implemented the principle of omudharabah. Furthermore, in the view of Islamic law, the operationalization was pursuant to the principles of mudharabah as determined by it. The implementation of mudharabah principle in the BRI Sharia on the grounds that with the application of it, people are more interested in the profit-sharing, where the bank and the customer do not feel disadvantaged (gains and losses are shared), because from the beginning of the contract, the profit sharing ratio is determined, so it will create distributive justice. Furthermore, the application of these savings product is charged with tax and zakat on the results obtained from the savings. With the operation of mudharabah savings at BRI Sharia branch of Surabaya, Muslims are expected to participate and be proactive in supporting and assist the development of this product. It means that Indonesian Muslims have been trying to avoid usury in their muamalah activities and more than that the bank are expected to develop and improve its products, especially funding product, so it can compete with the funding products of conventional banks, then the Islamic banks may be qualified.